Less Sugar and More Whole Grains in Infant Cereals: A Sensory Acceptability Experiment With Infants and Their Parents - Sanchez-Siles, Luisma; Román, Sergio; Haro-Vicente, Juan F.; Bernal, Maria Jose; Klerks, Michelle; Ros, Gaspar; Gil, Ángel (Frontiers in nutrition (Lausanne), 2022)
There is an urgent need to reduce sugar intake in early childhood. Commercial infant cereals are among the first solid foods introduced to infants at the beginning of the complementary feeding period in most countries. The aim of this study was to examine infants’ overall acceptability of low-sugar complementary cereals. To do so, a between-subjects experimental study with 165 parents and their infants aged 6–24 months was conducted where one group tested a high-sugar refined cereal (21 g/100 g), and the other a low-sugar cereal (<1 g/100 g) with 50% of whole grain, which represented a 95.2% decrease in sugar content. We found no significant differences between the two groups in terms of infants’ overall acceptability (infant’s reaction, estimated intake and relative intake). Importantly, infants’ reactions to high- and low-sugar cereals were not influenced by the time that infants had been consuming sweet cereals (15–25% sugar) before the experiment took place. In addition, parent’s overall liking and sensory evaluation (sweetness, color, taste, texture, and aroma) was positive and very similar in both groups. Overall, our findings show that it is feasible to reduce sugar content in infant cereals without sacrificing its sensory acceptability by infants and their parents. This represents a good opportunity for the infant food industry to adhere to current healthy and sustainable demands of lowering the sugar intake leading to important benefits in infants’ health, without compromising competitiveness in the market.